Audit Domain Acquire And Implement dengan Cobit 4.1 pada PT Erajaya Swasembada Tbk - Viany Utami Tjhin (ComTech: Computer, Mathematics and Engineering Applications, 2014)
The main priority aspect of information and communication technologies is given to control mechanisms, both internal and external in enterprises. It ensures that the reports and the decisions received and generated by the management will support their decision-making. The decisions have honesty and high integrity based on the results of the audit conducted on systems of information and communication technology. The objective of this research is to deliver audit reports of information systems for management and make recommendations on the audit findings in PT Erajaya Swasembada Tbk. Business processes studied included sales, purchasing, finance, and the warehouse. The system used was "Erajaya Live Application Server" and ERP (Enterprise Resource Planning)-based. This research used thedomain of COBIT 4.1: Acquire and Implement. The domain included several sub-domains, which were:identify automated solutions (AI1), acquire and maintain application software (AI2), acquire and maintain technology infrastructure (AI3), enable operation and use (AI4), procure IT resources (AI5), manage changes (AI6), and install and accredit solutions and changes (AI7). Data were collected from interviewing IT Department, distributing questionnaires to respondents, and observing the business processes of this enterprise. Research obtained 57 audit findings on IT implementation. The results of process reference model formulation are 3 findings on AI1subdomain, 5 findings on AI2subdomain, 9 findings on AI3subdomain, 6 findings on AI4 subdomain, 11 findings on AI5subdomain, 13 findings pada AI6subdomain, and 10 findings on AI7subdomain. The level of maturity model of this domain, Acquire and Implement (AI), was found on level 3.